Rosuvastatin prevents myocardial necrosis in an experimental model of acute myocardial infarction - Dourado,P.M.M. (2011)
Dyslipidemia is related to the progression of atherosclerosis and is an important risk factor for acute coronary syndromes. Our objective was to determine the effect of rosuvastatin on myocardial necrosis in an experimental model of acute myocardial infarction (AMI). Male Wistar rats (8-10 weeks old, 250-350 g) were subjected to definitive occlusion of the left anterior descending coronary artery to cause AMI. Animals were divided into 6 groups of 8 to 11 rats per group: G1, normocholesterolemic diet; G2, normocholesterolemic diet and rosuvastatin (1 mg·kg-1·day-1) 30 days after AMI; G3, normocholesterolemic diet and rosuvastatin (1 mg·kg-1·day-1) 30 days before and after AMI; G4, hypercholesterolemic diet; G5, hypercholesterolemic diet and rosuvastatin (1 mg·kg-1·day-1) 30 days after AMI; G6, hypercholesterolemic diet and rosuvastatin (1 mg·kg-1·day-1) 30 days before and after AMI. Left ventricular function was determined by echocardiography and percent infarct area by histology. Fractional shortening of the left ventricle was normal at baseline and decreased significantly after AMI (P < 0.05 in all groups), being lower in G4 and G5 than in the other groups. No significant difference in fractional shortening was observed between G6 and the groups on the normocholesterolemic diet. Percent infarct area was significantly higher in G4 than in G3. No significant differences were observed in infarct area among the other groups. We conclude that a hypercholesterolemic diet resulted in reduced cardiac function after AMI, which was reversed with rosuvastatin when started 30 days before AMI. A normocholesterolemic diet associated with rosuvastatin before and after AMI prevented myocardial necrosis when compared with the hypercholesterolemic condition.